Assessing content validity of enterprise architecture adoption questionnaire (EAAQ) among content experts - Ahmad N.A.; Drus S.M.; Kasim H.; Othman M.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Surveys; Content Validity; Content validity indices; Enterprise Architecture; Internal consistency; Measurement items; Psychometric properties; Quantitative approach; Validation process; Industrial electronics